Investigating University Students’ Attitudes towards Learning the English Language - Aisha Parvaiz; Dr. Syed Hyder Raza Shah; Sanam Gul (Dialogue Social Science Review (DSSR), 2025)
Attitudes towards language learning play a crucial role in the overall success of the acquisition process. Positive or negative perceptions can significantly influence learners’ motivation, engagement, and performance. This study investigates university students' attitudes towards learning the English language, with a particular focus on identifying any significant differences based on gender and institutional affiliation. The research was conducted at the University of Sanghar, involving a purposive sample of 97 undergraduate students who use English as a medium of instruction. The study employed a quantitative research design, and data were collected through a structured questionnaire. Statistical analysis was carried out using SPSS software to assess the general trends in learners’ attitudes and to examine any demographic variations. The findings indicate that the participants generally possess a positive attitude towards learning English, reflecting a high level of acceptance and motivation to develop proficiency in the language. Moreover, the analysis revealed no statistically significant differences in attitudes between male and female students, nor between students from different departments or faculties within the university. These results suggest a consistent and favorable perception of English language learning across the study sample. The study concludes by emphasizing the importance of nurturing such positive attitudes through supportive institutional policies and effective instructional strategies, which can further enhance students’ language learning experiences. The findings may also inform curriculum developers and educators aiming to improve English language teaching at the university level in similar contexts. Keywords: Attitudes, Gender, cognitive component, affective component, behavioral component.